Bounds for blow-up time in a semilinear parabolic problem with variable exponents - ABITA, Rahmoune; BENYATTOU, Benabderrahmane (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
This report deals with a blow-up of the solutions to a class of semilinear parabolic equations with variable exponents nonlinearities. Under some appropriate assumptions on the given data, a more general lower bound for a blow-up time is obtained if the solutions blow up. This result extends the recent results given by Baghaei Khadijeh et al. [8], which ensures the lower bounds for the blow-up time of solutions with initial data ' (0) = R u0 kdx, k = constant. Mathematics Subject Classification (2010): 35K55, 35K60, 35B44, 74G45. Received 28 August 2019; Accepted 21 April 2020.